Role of Active Components of Medicinal Food in the Regulation of Angiogenesis - Pan, Dezhi; Gong, Xue; Wang, Xiaoqin; Li, Minhui (Frontiers in Pharmacology, 2021)
Angiogenesis refers to the formation of new blood vessels from the endothelial cells of existing arteries, veins, and capillaries. Angiogenesis is involved in a variety of physiological and pathological processes, such as the formation of malignant tumors and development of atherosclerosis and other diseases. However, most of the anti-angiogenic drugs clinical limitations. In recent years, many studies have shown that the active components of food have a certain regulatory effect on angiogenesis and negligible clinical limitations. With more and more attention paid to the medicine and food homology, exploring the effect of active food components on angiogenesis is of great significance. In this paper, we discuss the source, composition, pharmacological activity, and mechanism of action of certain active components of medicinal food in detail. These could help prevent angiogenesis-related complications or provide a basis for healthier dietary habits. Our review can provide a theoretical basis for the research and development of highly efficient anti-angiogenic drugs with low toxicity.